A revision of the Chinese species of Cyamophiliopsis (Hemiptera: Psylloidea: Psyllidae) associated with Spiraea (Rosaceae) - Luo, Xinyu; Li, Fasheng; Cai, Wanzhi (Zootaxa, 2015)
Cyamophiliopsis is a small genus restricted to the Palaearctic Region and associated with Spiraea spp. (Rosaceae). In the present work, following five species are recognized in China: C. pseudofasciata sp. nov., C. sarmatica, C. spinosa sp. nov., C. xinjiangana sp. nov. and C. zaisani. Cyamophiliopsis is diagnosed, redescribed in detail, and its phylogenetic relationships are discussed. All the species are described or redescribed, and the fifth instar immature of C. zaisani is described for the first time. Nomenclatorial problems are discussed concerning the Far East Russian Psylla spiraee which is transferred to Cyamophiliopsis as C. spiraee comb. nov.